Theoretical and Experimental Investigation of the Antioxidation Mechanism of Loureirin C by Radical Scavenging for Treatment of Stroke - Ye-Shu Liu; Guo-Ying Zhang; Yue Hou (Molecules, 2023)
Recent pharmacological studies have shown that dragon’s blood has an anti-cerebral ischemia effect. Loureirin C (LC), a kind of dihydrochalcone compound in dragon’s blood, is believed to be play an important role in the treatment of ischemia stroke, but fewer studies for LC have been done. In this paper, we report the first experimental and theoretical studies on the antioxidation mechanism of LC by radical scavenging. The experimental studies show that LC has almost no effect on cell viability under 15 μM for the SH-SY5Y cells without any treatments. For the SH-SY5Y cells with oxygen and glucose deprivation-reperfusion (OGD/R) treatment, LC increased the viability of SH-SY5Y cells. The results of 2′,7′-Dichlorodihydrofluorescein diacetate (DCFH-DA) and MitoSox Red experiments indicate that LC is very efficient in inhibiting the generation of the intracellular/mitochondrial reactive oxygen species (ROS) or removing these two kinds of generated ROS. The density functional theory (DFT) calculations allowed us to elucidate the antioxidation mechanisms of LC. Fukui function analysis reveals the radical scavenging of LC by hydrogen abstraction mechanism, the complex formation by e-transfer, and radical adduct formation (RAF) mechanism. Among the H-abstraction, the complex formation by e-transfer, and radical adduct formation (RAF) reactions on LC, the H-abstraction at O-H35 position by OH• is favorable with the smallest energy difference between the product and two reactants of the attack of OH• to LC of −0.0748 Ha. The bond dissociation enthalpies (BDE), proton affinities (PA), ionization potential (IP), proton dissociation enthalpy (PDE), and electron transfer enthalpy (ETE) were calculated to determine thermodynamically preferred reaction pathway for hydrogen abstraction mechanism. In water, IP and the lowest PDE value at O3-H35 position are lower than the lowest BDE value at O3-H35 position; 41.8986 and 34.221 kcal/mol, respectively, indicating that SEPT mechanism is a preferred one in water in comparison with the HAT mechanism. The PA value of O3-H35 of LC in water is −17.8594 kcal/mol, thus the first step of SPLET would occur spontaneously. The minimum value of ETE is higher than the minimum value of PDE at O3-H35 position and IP value, 14.7332 and 22.4108 kcal/mol, respectively, which suggests that the SEPT mechanism is a preferred one in water in comparison with the SPLET mechanism. Thus, we can draw a conclusion that the SEPT mechanism of is the most favorite hydrogen abstraction mechanism in water, and O-H35 hydroxyl group has the greatest ability to donate H-atoms.